Information hiding 13th International Conference, IH 2011, Prague, Czech Republic, May 18-20, 2011, revised selected papers - Filler, Tomas; Pevny, Tomas; Craver, Scott; Ker, Andrew (Lecture notes in computer science, 2011)
This book contains the thoroughly refereed post-conferernce proceedings of the 13th Information Hiding Conference, IH 2011, held in Prague, Czech Republic, in May 2011. Included in this volume are 23 carefully reviewed papers that were selected out of 69 submissions. The contributions are organized in topical sections on: fingerprinting, anonymity and privacy, steganography and steganalysis, watermarking, digital rights management and digital forensics, and digital hiding in unusual context. Also included are the papers that were presented as part of the special session dedicated to the BOSS (Break Our Steganographic System) contest.